Trade Costs in Services: Firm Survival, Firm Growth and Implied Changes in Employment - Elisabeth Christen; Michael Pfaffermayr; Yvonne Wolfmayr (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper provides new insight into the firm-level employment impacts of trade cost changes at the industry level in the Austrian services sector. We apply a two-part model of firm survival (exit) and firm growth. Separate regressions for firm entry rates at the industry-region level complete the picture of total trade-induced net job creation. We implement the trade cost measure introduced by Chen and Novy (2011) and base it on own estimates of industry specific substitution elasticities. Falling trade costs in the Austrian services sector over the period 2000 to 2014 resulted in net job creation of about 19,000 jobs accounting for 9.5 percent of overall job flows in the sector. The smallest and least productive firms contract while large and productive firms expand as predicted by theory. Most adjustments occur at the extensive margin due to changes in the probability of firm survival.
Keywords: C15; C21; C25; C23; C26; F14; F16; F66; J21; D21; L20; L80; 330; services trade; trade costs; elasticity of substitution; firm-level evidence; heterogenous firms; gravity model; job flows; trade and employment